Teaching English to Children: Conclusions on a Study - Flor María Arteaga; Alicia Hidalgo (Asociación Colombiana de Profesores de Ingles, 2016)
The English teaching and learning process is a topic of great importance now in Colombia. Primary schools are implementing English as a foreign language in their curriculum. In different seminars teaching English to children has been discussed, and a great deal of uncertainty can be observed in primary school English teachers. They are unsure on how to approach the teaching of a foreign language to children since they have been trained on how to teach English to high school students. Parents complain that children do not like English and they argue that it is the fault of the English teachers. In the Nariño University at Pasto, an experience on this topic has taken place. Thirty children between 6 and 10 years of age are attending English classes. These students receive 10 hours of instruction per week. These 30 students are divided into 2 groups and have already approved five levels of English, each level lasting one semester.